Current Practices and Opportunities for More Sustainable Public Food Procurement: A Qualitative Study among Danish Municipalities and Regions - Anne Dahl Lassen; Anne Vibeke Thorsen; Ellen Trolle (Foods, 2023)
Public food procurement has been emphasized as a powerful tool to promote a healthier and more sustainable food system, but there is still a long way to go to reach full potential. This study aimed to investigate practices and opportunities for sustainable and healthy public food procurement. A qualitative cross-sectional study was performed among Danish municipalities and regions stratified and randomly selected to cover standard practice (n = 17). In addition, interviews were performed among selected best-practice municipalities (n = 5) providing examples of ambitious goals and well-defined processes for obtaining sustainable food procurement. Large differences were observed in the cross-sectional analysis in relation to policy support and goals for sustainable food procurement, including organic purchase. Generally, there was a great attentiveness to reduce food waste and many valued the use of local food, especially among rural municipalities, whereas experience with climate impact reduction and shifts towards more plant-based menus was still in an early implementation stage. Results suggest a possible synergy effect between the use of organic food and efforts to reduce food waste and climate impact and emphasize the importance of local government policies to promote healthy and sustainable food procurement. Enabling factors to move sustainable food procurement forward are discussed.